Assessment of the cable television industry in Iloilo City - Catedral, Roger; Hofilena, Eduardo; Ledesma, Raissa Ann.; Tansi, Joeven (1997.)
Most businesses today regard customers' satisfaction with more interest and vitality. Such a policy works ina manner that if customers are satisfied with the over-all performance of a servicing company, then gaining profit is rest assured. This has also been applied by firms composing the cable television industry of the Philippines. Highlighting on cable television three business entities namely Sun, Sky and Cable Star have provided cable television, subscription, and related products and services to individuals and other business establishments in Iloilo. This event called for a necessary study and evaluation of the firms performance - if they indeed have satisfied their subscribers with their products and services. Both sides (The companies' and the subscribers') were taken into consideration. analyses and findings of the study will be in relation to the key elements: target market, products and services, subscribers' standards, and subscribers problems. all these are discussed extensively in this research paper. Plus, feasible recommendations are also given.
Research Study (BA 200-Business Research). -- Iloilo City : University of the Philippines Visayas - College of Management, March 24, 1997.